Formation of self-assembled supramolecular polymers by anti-electrostatic anion–anion and halogen bonding interactions. Issue 52 (3rd June 2020) - Zapata, Fabiola; González, Lidia; Bastida, Adolfo; Bautista, Delia; Caballero, Antonio
Abstract : The cooperative action of anti-electrostatic anion–anion and halogen-bonding interactions serve as a driving force for the formation of self-assembled supramolecular polymers. Abstract : We report here the formation of self-assembled supramolecular polymers in which the cooperative action of anti-electrostatic anion–anion and halogen-bonding interactions serve as a powerful driving force for the formation of large supramolecular polymers. DOSY-NMR, DLS, TEM, SEM and X-ray experiments provide evidence of the formation of supramolecular structures in solution and solid state.